Pengaruh Manajemen Keluarga, Struktur Kepemilikan Keluarga, Struktur Modal dan Invesment Opportunity Set (IOS) Terhadap Kinerja Perusahaan (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2017-2022) - Muhammad Abdul Jabar; Mahatma Kufepaksi; Nindytia Puspitasari Dalimunthe (Departement of Mathematics Education, 2024)
A family company or family business is a business in which two or more family members are directly involved to have ownership and become the main control of the business. The study examined the effect of family management, family ownership structure, capital structure and investment opportunity set on company performance. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2022 and a sample of 22 companies using purposive sampling techniques. By using multiple linear regression for panel data and using data processing software in the form of Eviews, this study found that family management and family ownership structure did not affect company performance, capital structure had a negative and significant effect on company performance and investment opportunity set had a positive and significant effect on company performance.